RF-MEMS tunable interdigitated capacitor and fixed spiral inductor for band pass filter applications - Bade, L.A. (American Institute of Physics Inc., 2016)
This research presents the tunable Radio Frequency Micro Electromechanical Systems (RF-MEMS) coupled band-pass filter (BPF), which possess a wide tuning range and constructed by using the Chebyshev fourth degree equivalent circuit consisting of fixed inductors and interdigitated tunable capacitors. The suggested method was authenticated by designing a new tunable BPF with a 100 tuning range from 3.1 GHz to 4.9 GHz. The Metal Multi-User MEMS Process (Metal MUMPs) was involved in the process of design of this band-pass filter. It aimed to achieve the reconfiguration of frequencies and show high efficiency of RF in the applications that using Ultra Wide Band (UWB) such as wireless sensor networks. The RF performance of this filter was found to be very satisfactory due to its simple fabrication. Moreover, it showed less insertion loss of around 4 dB and high return loss of around 20 dB. Â© 2016 Author(s).